2016
DOI: 10.1016/j.hlc.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Exercise Capacity in Pulmonary Arterial Hypertension: A Systematic Review of Clinical Trials

Abstract: There is evidence to recommend the use of exercise training as an adjunct to medical treatment in PAH. More clinical trials and research are required to assess the effects of different types of exercise programs in patients with PAH, while focussing on strong exercise endpoints to quantify the improvements seen with exercise training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 46 publications
(112 reference statements)
5
62
0
2
Order By: Relevance
“…This emerging data has been seen specifically in the WHO group I PAH (Babu et al, 2016; Chan et al, 2013). Our study shows exercise tolerance improvements in terms of speed in mph and increased duration of exercise across multiple etiologies of PHTN after a course of structured PR.…”
Section: Discussionmentioning
confidence: 83%
“…This emerging data has been seen specifically in the WHO group I PAH (Babu et al, 2016; Chan et al, 2013). Our study shows exercise tolerance improvements in terms of speed in mph and increased duration of exercise across multiple etiologies of PHTN after a course of structured PR.…”
Section: Discussionmentioning
confidence: 83%
“…104107 One main conclusion was that improvements in 6MWD varied with different exercise modalities, favoring a combination of aerobic resistance and respiratory muscle training. 105 Further evidence comes from two systematic reviews with meta-analyses which included controlled interventional studies published up to 2013 106 and prospective interventional studies published up to 2015. 107 The meta-analyses demonstrated that ET led to a significant increase in 6MWD with a mean improvement of 72 m versus controls and 53 m versus baseline, respectively, accompanied by slight increases in peak VO 2 (2.2 mL/kg/min versus controls and 1.8 mL/kg/min versus baseline, respectively).…”
Section: Therapeutic Effects Of Exercisementioning
confidence: 99%
“…The complexity of this disease, including high pulmonary pressures, ventilation-perfusion abnormalities, dysfunction in peripheral oxygen extraction and respiratory muscle dysfunction makes the benefit and safety of exercise therapy difficult to predict. Meta-analysis of studies published between 1980 and 2015 revealed 15 studies of moderate to good quality (using the Downs and Black Quality Index) comprising 477 total patients [51]. Exercise training resulted in significant increase in exercise capacity, modest improvement in VO2 (1–2ml/kg-min) and functional class, and minimal adverse effects.…”
Section: The Evidence Behind Current Practicementioning
confidence: 99%